Evaluation of urethral thickness using ultrasonography in healthy small-breed dogs - Kim, Geunha; Ji, Yewon; Choo, Donghyeok; Kim, Sung-Soo; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2022)
Urethral thickness measurements can be indicative of the pathological state of a patient; however to the best of our knowledge, no measurement reference range has been established in small-breed dogs. This study aimed to establish reference ranges for total urethral thickness and urethral wall thickness in healthy small-breed dogs; “urethral wall thickness” was assumed to be 1/2 of the “total urethral thickness.” We also analyzed the differences in total urethral thickness between breeds, sexes, and sterilization status, and investigated the correlation between body weight (BW) and total urethral thickness. Total urethral thickness was measured by ultrasonography in 240 healthy small-breed dogs. In both female and male dogs, the thickness was measured in the mid-sagittal plane. In female dogs, it was measured immediately before the pelvic bone. In male dogs, it was measured caudal to the prostate and cranial to the pelvic bone. The total urethral thickness we measured is the total thickness of the collapsed urethra, which is the sum of the thicknesses of the dorsal and ventral urethral wall. The mean value of total urethral thickness was 3.15  0.83 mm (urethral wall thickness, 1.58  0.41 mm) in 240 small-breed dogs. The total urethral thickness was significantly greater in male dogs than in female dogs (p < 0.001), even when compared among the same breeds (p < 0.05). The mean value of the total urethral thickness in females was 2.78  0.60 mm (urethral wall thickness, 1.39  0.30 mm), and 3.53  0.86 mm (urethral wall thickness, 1.76  0.43 mm) in males. There was very weak positive correlation between BW and total urethral thickness (R2 = 0.109; β = 0.330; p < 0.001). Intraobserver reliability measured by intraclass correlation coefficient (ICC) was 0.986 (p < 0.001) and interobserver reliability measured by ICC was 0.966 (p < 0.001). This is the first study to provide reference ranges of total urethral thickness and urethral wall thickness in small-breed dogs using ultrasonography, and is expected to be useful for urethral evaluation in veterinary diagnostic imaging.